2019
DOI: 10.1016/j.soard.2019.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Gastric sleeve resection as day-case surgery: what affects the discharge time?

Abstract: Background: Sleeve gastrectomy (SG), with its short operating time, is possible to perform as same-day surgery, with the most common reason for requiring overnight hospital stay being post-operative nausea and vomiting. Objective: To demonstrate the feasibility and safety of SG as same-day surgery with regards to complication rate. Additionally, the study aimed to evaluate factors determining the duration of hospital stay, such as type of anesthesia, time of procedure, degree of postoperative nausea and pain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Moreover, Tenconi et al (2008) found that patients' doubts about day surgery procedures or their insecurity feelings of the proposal of discharge within 24 hr were also important factors for delayed discharge. Conversely, Aftab et al (2019) reported that the anaesthesia type, procedure time, PONV and pain had no effects on delayed discharge in gastric sleeve resection cases undergoing day surgery. Although these studies above reported the risk factors for delayed discharge in day surgery cases, the heterogenicities such as varied definitions of delayed discharge and different surgery procedures contributed to the controversial results.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Tenconi et al (2008) found that patients' doubts about day surgery procedures or their insecurity feelings of the proposal of discharge within 24 hr were also important factors for delayed discharge. Conversely, Aftab et al (2019) reported that the anaesthesia type, procedure time, PONV and pain had no effects on delayed discharge in gastric sleeve resection cases undergoing day surgery. Although these studies above reported the risk factors for delayed discharge in day surgery cases, the heterogenicities such as varied definitions of delayed discharge and different surgery procedures contributed to the controversial results.…”
Section: Introductionmentioning
confidence: 98%
“…Discharge on the day of surgery was reported as feasible in selected patients [ 190 192 ]. However, there was some disagreement around the safety of same-day discharge [ 193 , 194 ].…”
Section: Resultsmentioning
confidence: 99%
“…Third, total intravenous anesthesia was administered throughout the surgery. So, the effect of inhalation anesthesia on gastrointestinal function was ruled out [7,28]. Forth, we found that fentanyl, oxycodone, and butorphanol allowed for equivalent analgesia.…”
Section: Table 1 Patients' Characteristics and Other Factormentioning
confidence: 92%